DIVERSITY OF APHYLLOPHORALES FUNGI ISOLATED FROM TANJUNG PUTING NATIONAL PARK, CENTRAL KALIMANTAN AND ITS POTENTIALITY FOR LIGNIN DECOMPOSITION - Typuk Artiningsih; Herwint Simbolon; Suhirman Suhirman; Mitsuru Osaki (BERITA BIOLOGI, 2000)
A total of fifty-three samples of fungal basidiocarp were collected from peat area in Tanjung Puting National Park, Central Kalimantan, Indonesia. These samples are mostly determined to genus until more studies are available.The fungi were isolated on CMA medium then the isolated strains were purified on PDA medium. The fungi belong to at least 3 families of Aphyllophorales, however there were a wide diversity in the genus with respect to macroscopic examination.An agar plate screening procedures was developed for the rapid selection of fungi and estimation of their capacity for lignin-decomposer. The test is based on the visualization and interpretation of the formation of halo zone or decolourization process in well-defined agar medium containing Poly R-478. The selected isolates were also tested in to rhemazol brilliant blue R salt (RBBR) medium. Five isolates had the ability to decolourize either Poly R-478 or RBBR. These isolates showed a qualitative lignin decomposition although a comparative study of selected fungi revealed the difference potentiality. The highest loss of lignin was 28.18% and attempts have been made to determine the unidentified fungi, which is resupinate type, by direct sequencing of 18s ribosomal DNA (rDNA).